2019
DOI: 10.1111/vco.12513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of outcome in dogs that undergo secondary amputation as an end‐point for managing complications related to limb salvage surgery for treatment of appendicular osteosarcoma

Abstract: Appendicular osteosarcoma (OSA) remains a prevalent musculoskeletal cancer in dogs and definitive local control followed by adjuvant cytotoxic chemotherapy is considered the gold standard approach. Several studies support surgical limb salvage as a means of local control with similar outcomes compared with limb amputation. Complications are well described for limb salvage but little is known of dogs that undergo secondary amputation as a result of complications and outcomes specific to this group. A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The remaining 32 patients elected for euthanasia after being diagnosed with a pathologic fracture, leading to the shorter survival time. Improved survival following amputation is a similar finding to a recent publication using a limb salvage surgical procedure as the initial primary treatment 2 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The remaining 32 patients elected for euthanasia after being diagnosed with a pathologic fracture, leading to the shorter survival time. Improved survival following amputation is a similar finding to a recent publication using a limb salvage surgical procedure as the initial primary treatment 2 …”
Section: Discussionsupporting
confidence: 83%
“…In these cases, a limb‐sparing treatment provides an alternative to amputation. Limb sparing surgery allows for resection of the tumour with the goal of maintaining a functional limb; however, complication rates following these surgeries range from 50% to 96% 2‐6 . Surgical options are limited to the distal radius, ulna, and diaphyseal lesions with poor results reported for limb sparing surgery for the humerus 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This approach was adopted in a study of risk factors for secondary amputation following limb salvage surgery for osteosarcoma in dogs but failed to find an association between R-classification and LR. 18 The difference though may be one of tumour biology where the mode of metastasis in AGASACA is primarily lymphatic while primarily hematogenous in bone sarcoma. This warrants further study and the inclusion of blood vessel or lymphatic invasion into the adequacy of histologic margin should be considered in AGASACA.…”
Section: Resultsmentioning
confidence: 99%
“…This may also reflect clinician selection bias unlikely to recommend amputation for patients with more advanced disease. A recent study reported a median survival of 205 days following secondary amputation following limb‐spare complications so it is not unreasonable to apply similar reasoning to secondary amputation following RT (Wustefeld‐Janssens et al., 2020). Additional factors evaluated against patient survival are summarised in Table 4.…”
Section: Discussionmentioning
confidence: 99%